The effects of sun intensity during pregnancy and in the first 12 months of life on childhood obesity - Christian Dustmann; Uta Schoenberg; Malte Sandner (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2022)
Obesity not only leads to immense medical costs associated with treating obesity-related illness but is also associated with lower employment prospects and earnings. This study shows that sunshine-induced vitamin D may have a preventive effect on obesity for children. It investigates the relation between sun intensity from pregnancy until infancy on obesity at age six, using population data of more than 600,000 children. Our findings show that the effects of sun intensity on subsequent obesity are concentrated in the first six months of life: 100 hours of additional sunshine over this period reduce overweight by 1.1 percent and severe obesity by 6.2 percent. We offer two main explanations for this pattern. First, infants' vitamin D levels are particularly sensitive to sunshine in the first six months of life, when lactation is highest. Second, the first six months of life are a sensitive period for later obesity, as this is the period when infants rapidly gain weight and adipose tissue develops.
Keywords: I18; I12; 330; Childhood Obesity; Prevention; Vitamin D